2018
DOI: 10.1177/0192512118757128
|View full text |Cite
|
Sign up to set email alerts
|

Popular conceptions of democracy and democratic satisfaction in China

Abstract: Evaluating attitudes to democracy in an authoritarian political system is complex. Several surveys suggest that the majority of Chinese people feel satisfied with the level of democracy in China. In explaining this intellectual puzzle, this study addresses how different understandings of democracy influence satisfaction with the state of democracy. This study also investigates the relationships between liberal democratic values and popular conceptions of democracy, and between liberal democratic values and sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Our study shows that in those people, the positive effects of government's social performance on political trust attenuated, while the negative effects of government's political performance on political trust became stronger. In contrast to the older generations and less educated people, the younger generations and educated people tend to subscribe to the procedural perceptions of democracy (Shi, 2014;Zhai, 2018a). With inter-generational replacement, an increase in the population that views political rights as an essential component of democracy will have relevant implications for an authoritarian system's democratic transition in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study shows that in those people, the positive effects of government's social performance on political trust attenuated, while the negative effects of government's political performance on political trust became stronger. In contrast to the older generations and less educated people, the younger generations and educated people tend to subscribe to the procedural perceptions of democracy (Shi, 2014;Zhai, 2018a). With inter-generational replacement, an increase in the population that views political rights as an essential component of democracy will have relevant implications for an authoritarian system's democratic transition in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Today, there is no country that publicly opposes democracy but autocratic countries try to manipulate the concept of democracy for serving undemocratic rules. Existing literature has shown that the Chinese public has a high level of support for democracy (Shi, 2000; Shi and Lu, 2010; Zhai, 2018a). Yet, pro-democratic attitudes have not resulted in a widespread public struggle for democracy or democratic movements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It does not only fulfil the basic requirements of information but also connect the people with the world of knowledge (Anwar & Jan 2010). The citizen's satisfaction with democracy is an interlinked universal process that develops a true political process (Zhai, 2018). Democracy requires a particular physical place and arrangements for democratic concerts.…”
Section: Introductionmentioning
confidence: 99%
“…Citizens who think political and electoral rights are basic requirements of democracy are satisfied with the current democratic system, where social media penetration has a significant relation with democracy. It provides a platform for the participant's democratic activities (Zhai, 2018;Beetham, 2004;Herrmann, 2016;Jha & Kodila-Tedika, 2019).…”
Section: Introductionmentioning
confidence: 99%